Characterisation of PolydimethylSiloxane(PDMS) by liquid-state NMR spectroscopy - Haddady Khelejan, Solmaz (Jihočeská univerzita, 2021)
This work analyzes how two liquid /viscose base materials (Base and Curing Agent by Ecoflex ?), after putting together and polymerization, will produce silicones. We want to show how vinyl groups are consumed and how methyl attached groups increase during this process. And how Base and Curing Agent are different.
Characterisation of PolydimethylSiloxane(PDMS) by liquid-state NMR spectroscopy
Keywords: silicone elastomer; polydimethylsiloxane; PDMS; polymerization; NMR spectrometry-; silicone elastomer; polydimethylsiloxane; PDMS; polymerization; NMR spectrometry